Middermal Elastolysis: Dermal Fibroblasts Cooperate with Inflammatory Cells to the Elastolytic Disorder - De Cunto, Giovanna; Lamberti, Arianna; de Santi, Maria Margherita; Miracco, Clelia; Fimiani, Michele; Lungarella, Giuseppe; Cavarra, Eleonora (Mediators of Inflammation, 2017)
Little is known about the cause and pathophysiology of middermal elastolysis (MDE). In this condition, variable inflammatory infiltrate may be present or not together with loss of elastic fibres in the middermis that spares both papillary and lower reticular dermis. MDE may be a consequence of abnormal extracellular matrix degradation related to an imbalance between elastolytic enzymes released from inflammatory and resident cells and their naturally occurring inhibitors. However, the cause of this imbalance is still an object of investigation. In order to shed light on the role of fibroblasts in MDE, we used fibroblast cultures from MDE and control subjects to evaluate matrix metalloproteinases (MMPs) and their major inhibitor TIMP-1, which in combination with neutrophil or macrophage proteases released in inflamed areas may influence the elastolytic burden. We demonstrate that fibroblasts derived from MDE produce in vitro low levels of TIMP-1, the major inhibitor of MMPs. Elevated levels of MMP-2, MMP-14, and TIMP-2 capable to activate in a cooperative manner pro-MMP-2 are present in MDE tissue samples. Additionally, significant reaction for MMP-1 is present in the same MDE areas. These data all together suggest that ECM changes in MDE are due to cooperation of different cell populations (i.e., inflammatory cells and fibroblasts).